Synthesis, Structural Characterization and DNA Binding Studies on Transition Metal Complexes with 2-Formylpyridine Benzoylhydrazone - Anuja, K.; Reddy, K. Hussain; Srinivasulu, K.; Dhanalakshmi, D. (Asian Journal of Chemistry, 2019)
The hydrazone ligand, 2-formylpyridine benzoylhydrazone (FPBH) has been used to synthesize copper(II), nickel(II) and cobalt(II) complexes and characterized by elemental analyses, mass spectra, molar conductivity data IR, UV-visible spectroscopy. The complexes are found to have general formula M(FPBH)2 (where, M = Cu(II), Ni(II) and Co(II). Further the copper complex is investigated using ESR spectra. The spin Hamiltonian, orbital reduction and bonding parameters are calculated for the complex. The complex, Ni(FPBH)2 is structurally characterized based on single crystal X-ray crystallography. The complex crystallizes in monoclinic space group P21/c with a = 11.2632(2) Å, b = 8.8958(2) Å, c = 23.0834(5) Å, α = 90°, β = 90.858(2)°, γ = 90°, V = 2312.59(8) Å3 and Z = 4 with central Ni(II) ion in distorted octahedral structure coordinated by two tridentate FPBH ligand. The interactions of these complexes with calf thymus DNA have been investigated using absorption spectrophotometry. The copper complex binds more strongly than either nickel or cobalt complexes.